Implementasi Pendekatan Saintifik Pada Pembelajaran Menulis Teks Prosedur Kompleks Di SMK Negeri 1 Miri Sragen - KUSUMAWATI, YULI, Prof. Dr. Markhamah, M.Hum, Prof. Dr. Harun Joko Prayitno, M.Hum (2017)
This study aimed to describe the implementation of the teaching of writing with a scientific approach. The study used a qualitative descriptive study. The data in this study is a learning process and interviews. Sources of data in this study were teachers and students. Data were obtained from observations and interviews. Data were analyzed using the techniques of data collection, reduction, and conclusions. The results of this study is that the first meeting of learning to write text complex procedures, in this study has applied the scientific method even though this method is not fully achieved in the first lesson. Phase one has yet achieved is the stage of data collection and associates. The learning objectives at the first meeting has also been achieved. The results of observations of learning to write in the second meeting went smoothly. Teacher looks still use the lecture method so impressed that teachers still play an active role. When the teacher explained, students are bored and sleepy. The scientific method in this second study has been 2 used, the stage to try and associate it appears. Not much different from the first meeting. All elements in the scientific approach has been implemented. The results of the third meeting of observation can be inferred teaching of writing goes well and smoothly. The learning activities are in accordance with lesson plans created by teachers. All activities related to the scientific approach which includes a five-M has been applied. Activity observe, ask, gather information, associates, and communication has been applied to all the teachers.